2017
DOI: 10.1556/2006.6.2017.075
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the differential effects of social networking site addiction and Internet gaming disorder on psychological health

Abstract: Background and aimsPrevious studies focused on examining the interrelationships between social networking site (SNS) addiction and Internet gaming disorder (IGD) in isolation. Moreover, little is known about the potential simultaneous differential effects of SNS addiction and IGD on psychological health. This study investigated the interplay between these two technological addictions and ascertained how they can uniquely and distinctively contribute to increasing psychiatric distress when accounting for potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
157
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 79 publications
18
157
2
10
Order By: Relevance
“…Taken together, these findings could potentially illustrate common clinical course and shared etiology between different types of addictive behaviors. Furtherly, these results lend support to previous studies suggesting some underlying common risk factors between several technological addictions and related behaviors (Andreassen et al, 2016;Grant, Potenza, Weinstein, & Gorelick, 2010;Pontes, 2017;Robbins & Clark, 2015) and provide context to further understand why empirical studies often report positive associations between various addictive technological behaviors (Andreassen et al, 2016;Király et al, 2014;Pontes, 2017).…”
Section: Resultssupporting
confidence: 86%
“…Taken together, these findings could potentially illustrate common clinical course and shared etiology between different types of addictive behaviors. Furtherly, these results lend support to previous studies suggesting some underlying common risk factors between several technological addictions and related behaviors (Andreassen et al, 2016;Grant, Potenza, Weinstein, & Gorelick, 2010;Pontes, 2017;Robbins & Clark, 2015) and provide context to further understand why empirical studies often report positive associations between various addictive technological behaviors (Andreassen et al, 2016;Király et al, 2014;Pontes, 2017).…”
Section: Resultssupporting
confidence: 86%
“…Petry et al (2014) suggested that "establishing the psychometric properties of instruments assessing these nine [IGD] criteria should begin using a cross-cultural perspective", and because gaming behavior may differ across cultures, studies examining the psychometric properties of the IGDS9-SF in distinct countries around the world are needed ). This notion is partly supported by a recent study on the IGDS9-SF that investigated the cross-cultural feasibility of the scale across gamers from the United States of America (USA), India, and the United Kingdom (UK) (Pontes et al, 2017). Although the one-factor structure of the IGD construct was supported, crosscountry variations were demonstrated and reflected on IGD items assessing preoccupation/salience, tolerance, deception, gaming escapism/mood modification, as well as daily activities' impairment related to gaming.…”
Section: Introductionmentioning
confidence: 87%
“…Based on the approach utilized by previous research using the IGDS9-SF (e.g., de Palo et al, 2018;Gomez et al, 2018;Pontes, 2017;Stavropoulos et al, 2018), participants' answers to the IGDS9-SF items as (5) "very often" were operationalized as endorsement of a criterion. Thus, the prevalence of potential IGD was about 0.96% (n = 12) for the whole sample and around 2.57% (n = 8) among esports gamers.…”
Section: Prevalence Rates Of Igdmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews and empirical studies investigating the psychometric assessment of IGD were conducted (see King et al, 2013;Pontes andGriffiths, 2014, 2015b). Due to the ongoing debate and unofficial…”
Section: Introductionmentioning
confidence: 99%